Priority option pricing in an M/M/m queue - Printezis, A.; Burnetas, AN (Operations Research Letters, 2008)
We study a system where the service provider offers priority options. We identify the optimal option pricing policy, by deriving the optimal number a customer would buy and the customer's exercise policy as a function of system congestion, options remaining, time to expiration and possibility of balking.
Keywords: Customer satisfaction; Optimal numbers; Option pricing; Priority pricing; Service options; Service providers; Systems engineering